Pleural Fluid Has Pro-Growth Biological Properties Which Enable Cancer Cell Proliferation - Asciak, Rachelle; Kanellakis, Nikolaos I.; Yao, Xuan; Abd Hamid, Megat; Mercer, Rachel M.; Hassan, Maged; Bedawi, Eihab O.; Dobson, Melissa; Fsadni, Peter; Montefort, Stephen; Dong, Tao; Rahman, Najib M.; et al. (Frontiers in Oncology, 2021)
Objectives Patients with malignant pleural mesothelioma (MPM) or pleural metastases often present with malignant pleural effusion (MPE). This study aimed to analyze the effect of pleural fluid on cancer cells. Materials and Methods Established patient-derived cancer cell cultures derived from MPE (MPM, breast carcinoma, lung adenocarcinoma) were seeded in 100% pleural fluid (exudate MPM MPE, transudate MPE, non-MPE transudate fluid) and proliferation was monitored. In addition, the establishment of new MPM cell cultures, derived from MPE specimens, was attempted by seeding the cells in 100% MPE fluid. Results All established cancer cell cultures proliferated with similar growth rates in the different types of pleural fluid. Primary MPM cell culture success was similar with MPE fluid as with full culture medium. Conclusions Pleural fluid alone is adequate for cancer cell proliferation in vitro, regardless of the source of pleural fluid. These results support the hypothesis that pleural fluid has important pro-growth biological properties, but the mechanisms for this effect are unclear and likely not malignant effusion specific.